How we see ourselves - Cohen, David, 1946- author. Link
1 online resource (xii, 126 pages)
Keywords: "This light-hearted and entertaining book, authored by top psychologist David Cohen, explores the influences and impacts on our perception of body image, examining the power of appearance and the psychology behind how we think and feel about ourselves physically. Packed with scientific findings alongside historical anecdotes and humorous insights, the book first looks at the history of body image and appearance, and how ideals of beauty have changed over time. It goes on to note the rise of the beauty and fashion industries, looking at how society, culture and the media can affect body image. The final section deals with issues of body dissatisfaction and the treatments and therapy available for those struggling with body image and mental health. Along the way, readers will meet a cast of characters from Elizabeth I, a daring, medieval Welsh poet, an Egyptian mummy with the first known tattoo, Paul F. Schilder who pioneered the study of body image, and the brave recipients of the first face transplants, among many more. In his trademark engaging style, Cohen offers a rich account of the psychology of body image through the ages and through the lifespan. It is valuable reading for students of psychology and professionals and therapists aiming to promote body positivity"--